ABORDAGENS DE GÊNERO EM LIVROS DIDÁTICOS DE SOCIOLOGIA PARA O ENSINO MÉDIO - RAMOS, ROKELY SCHEIFITER DE (2018)
This dissertation features the results of an investigation into gender education by means of comparative analysis, approaching, and gender representation in three Sociology schoolbooks for high school students: “Sociology” (VARIOS AUTORES, 2006), “Modern Times, Sociology Times” (BOMENY; MEDEIROS, 2010), and “Sociology for High School” (TOMAZI, 2013). The purpose of this research is analyzing how gender contents are built and signified within the discipline of Sociology in High School, hence unfolding the implications of schoolbooks in regard to this process, emphasizing the way materials affect the following aspects: the questioning of binary vision, the comprehension of gender as a social and cultural construct; the development of a perception of how power relations are disseminated and (re)produced by society and how alterity becomes important in overcoming prejudice, in the process of identity building and the consideration of otherness. The methodology we employ is exploratory, comparative and inductive, with a bibliographic revision about: the concept of gender, education, and the attributions of schoolbooks in regard to Sociology teaching; followed by description and analysis of the schoolbooks and the qualitative presentation of results. For this purpose, we adopt a sociological theoretical approach, articulating the contribution of both cultural and gender studies. Also, we highlight critical-reproductivist theories as we proceed to understand the Education Institution and the schoolbook as a pedagogical, marketing artifact, as well as a social construct. This study consists of a reflection about schoolbooks in the educational process, the relevance of gender learning in order to promote equality/alterity, and the denaturalizing role performed by Sociology, hence our proposal to aggregate knowledge to such a widely debated subject in the fields of diversity and education. Keywords: Gender, Education, Sociology, Schoolbooks.